Alfabetização no ensino fundamental de nove anos: avaliação discente e suas implicações para as práticas pedagógicas - Guarnieri, Maria Regina [UNESP]; Vieira, Luciene Cerdas [UNESP] (My University, 2010)
This paper focuses data from discussions done with teachers who work with the three early years of nine-years elementary chool, in two Municipal schools of São Paulo inland, in order to investigate the students’ literacy degree. Considering a test applied to students of three early years of those schools, this study deals with the literacy performance results of 153 children of third school year. It also relates data of this test with some aspects that have characterized the literacy teachers’ practices. Initially, it presents considerations about the literacy process in extent of nine-years elementary school and some implications for the teachers’ practices. Then, it emphasizes the test results of third year students, pointing out what skills were already developed by them in literacy process and what skills must be improved. Results show that those children are not literated. They demonstrate difficulties in the appropriation of reading and writing skills, even in the third school year. It suggests the teachers’ need to reorganize their practices in classroom and to revise students’ literacy process, allowing to every student the full appropriation of reading and writing.

Este artigo focaliza dados oriundos de discussões com professoras que atuam nos três primeiros anos do ensino fundamental de nove anos, em duas escolas municipais do interior paulista, com o objetivo de diagnosticar a situação dos alunos em relação à alfabetização. Por meio de avaliação aplicada a alunos que frequentam os três anos iniciais nessas escolas, o texto aborda o desempenho de 153 crianças do terceiroano escolar na alfabetização. Relaciona também os dados dessa avaliação com aspectos que vêm caracterizando as práticas das professoras alfabetizadoras. Inicialmente, apresenta apontamentos sobre o processo de alfabetização no âmbito do ensino fundamental de nove anos e algumas implicações para as práticas das professoras. Em seguida, destaca os resultados da avaliação dos alunos das turmas de terceiro ano, indicando capacidades já desenvolvidas por eles na alfabetização e outras a serem consolidadas. Os resultados mostram que essas crianças não se encontram alfabetizadas, o que revela atraso na apropriação de capacidades para a leitura e a escrita, embora estejam no terceiro ano escolar. Sugerem ainda a necessidade de as professoras reorganizarem suas práticas na sala aula e retomarem o processo de alfabetização, para oportunizar a todos os alunos a apropriação plena da leitura e da escrita.
Literacy in nine-years elementary school: students’ performances and its implications to pedagogical practices
Keywords: Literacy; Nine-year elementary school; Students’ performance; Teachers’ practices; Alfabetização; Desempenho dos alunos; Ensino fundamental de nove anos; Práticas de professoras